Serum Vitamin B12 and thyroid hormone levels in Saudi patients with multiple sclerosis - Fahd A Al-Khamis (Wolters Kluwer Medknow Publications, 2016)
Objectives: To determine the relationship between Vitamin B12 levels and thyroid hormones in patients with multiple sclerosis (MS). Materials and Methods: One hundred and ten patients with MS were recruited for this study after Institutional Review Board approval. All patients signed a written informed consent form and donated a single blood sample. Plasma Vitamin B12 levels, triiodothyronine (T3), and thyroxine (T4) hormone levels were measured. Data were analyzed using the Statistical Package for Social Sciences (SPSS) software. Results: Analysis of Vitamin B12 levels in 110 patients with MS revealed that 65% had normal levels of Vitamin B12 (200-900 pg/ml), 30% had low levels of Vitamin B12 (<200 pg/ml), and 5% high levels of Vitamin B12 (higher than 900 pg/ml). Further analysis of patients with low levels of Vitamin B12 revealed that this cohort exhibited a significantly high number of patients with low levels of the thyroid hormones triiodothyronine (T3) and thyroxine (T4) (P < 0.005). Conclusion: This study suggests a relationship between Vitamin B12 levels and thyroid hormones. This opens the possibility that the use of therapies that increase triiodothyronine (T3) and thyroxine (T4) levels might be beneficial to patients with MS.